Photo-oxidation-modulated refractive index in Bi2Te3 thin films. (6th December 2017) - Yue, Zengji; Chen, Qinjun; Sahu, Amit; Wang, Xiaolin; Gu, Min
Abstract: We report on an 800 nm femtosecond laser beam induced giant refractive index modulation and enhancement of near-infrared transparency in topological insulator material Bi2 Te3 thin films. An ultrahigh refractive index of up to 5.9 was observed in the Bi2 Te3 thin film in near-infrared frequency. The refractive index dramatically decreases by a factor of ~3 by an exposure to the 800 nm femtosecond laser beam. Simultaneously, the transmittance of the Bi2 Te3 thin films markedly increases to ~96% in the near-infrared frequency. The Raman spectra provides strong evidences that the observed both refractive index modulation and transparency enhancement result from laser beam induced photooxidation effects in the Bi2 Te3 thin films. The Bi2 Te3 compound transfers into Bi2 O3 and TeO2 under the laser beam illumination. These experimental results pave the way towards the design of various optical devices, such as near-infrared flat lenses, waveguide and holograms, based on topological insulator materials.